'All this is about is money and making sure that heads are on beds': Perceptions of payment by results in a therapeutic community. (June 2016) - Gosling, Helena
The aim of this article is to critically reflect upon some of the practical difficulties which surround the implementation of an outcome-focused payment initiative, colloquially referred to as Payment by Results (PbR), in a drug and alcohol service situated in the North of England. Drawing upon the findings of a longitudinal study in a residential rehabilitation service, the discussion illustrates some of the tensions and dilemmas which surround the introduction of increasingly business-orientated decisions within a person-centered environment that is designed to work alongside some of society's most troubled and troublesome individuals. To conclude, the article suggests that financially-driven processes (such as PbR) commodify the rehabilitative ideal, making service users and practitioners alike increasingly accountable to a counterintuitive fiscal endeavour.